Relationships between Thoroughbreds’ Contribution in the Pedigree and the Level of Fearfulness and Performance in Warmblood Stallions - Monika Budzyńska (Sciendo, 2018)
The aim of this study was to test the hypothesis that Thoroughbred (TB) ancestors blood percentage in a pedigree is a potential factor differentiating the level of fearfulness (based on behavior and heart rate (HR)) and performance scores in warmblood stallions. A total of 267 three-year-old warmblood stallions were subjected to the novel-object based test during their participation in the performance tests’ program. The effect of ancestors percentage contribution in the pedigree was analyzed by taking into account horses of four TB (<25.01, 25.01-50.00, 50.01-75.00, >75.00%) ancestor groups. It was found that the stallions with a higher proportion (>75.00%) of TB blood revealed higher values of HR measured at the riding hall just before the start of the fearfulness test. The results showed that the higher proportions of TB ancestors blood in the stallions’ pedigree were correlated with the higher values for total time to pass novel objects when led by a handler during the fearfulness test. Negative correlations were found between the TB percentage and the scores for character and trot evaluated by the trainer as well as rideability evaluated by the test rider. The fi ndings imply that a high proportion of Thoroughbreds in the pedigree may negatively infl uence some performance traits and increase fear reactivity in warmblood stallions.